2016
DOI: 10.1155/2016/2414769
|View full text |Cite
|
Sign up to set email alerts
|

Light and Electron Microscopic Studies on Prenatal Differentiation of Exocrine Pancreas in Buffalo

Abstract: The study was conducted on pancreas of 24 buffalo fetuses collected from abattoir and Veterinary clinics, GADVASU, Ludhiana. The buffalo fetuses were divided into three groups after measuring their CVRL, namely, group I (CVRL between 0 and 20 cm), group II (CVRL above 20 cm and up to 40 cm), and group III (CVRL above 40 cm) and their approximate age was calculated. The tissues were processed for light and ultrastructural studies. In group I, at 1.2 cm CVRL (34 days), the pancreas comprised tubules and solid ne… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
6
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(9 citation statements)
references
References 14 publications
3
6
0
Order By: Relevance
“…The acinar pancrease formed of pancreatic acinar cells which had a relatively large spherical nuclei with condensated heterochromatin at the periphery and prominent nucleoli that found eccentric to the nucleus. The shape of the acinar cells had some variation in which the current work reported the pyramidal cells, similar to that reported by (29) in large white Yorkshire pigs (Sus scrofa) and (11) in Egyptian one-humped camel Camelus dromedarius, while (15) described that there are some variation of acinar cell shape from columnar to pyramidal in buffalo.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…The acinar pancrease formed of pancreatic acinar cells which had a relatively large spherical nuclei with condensated heterochromatin at the periphery and prominent nucleoli that found eccentric to the nucleus. The shape of the acinar cells had some variation in which the current work reported the pyramidal cells, similar to that reported by (29) in large white Yorkshire pigs (Sus scrofa) and (11) in Egyptian one-humped camel Camelus dromedarius, while (15) described that there are some variation of acinar cell shape from columnar to pyramidal in buffalo.…”
Section: Discussionsupporting
confidence: 90%
“…The small clusters of pancreatic endocrine cells were first depicted by Paul Langerhans in 1869, after whom they were named as "Islets of Langerhans". From that point forward, numerous morphological examinations have been completed utilizing the different histological and ultrastructural techniques in numerous animal species such as camel (10-13), bovine (14,15), feline (16), monkey (17), rabbit (18), rodent, canines and Guinea pig (19), mice (20), and rat (21)(22)(23). The endocrine pancreas has likewise been concentrated in-non mammalian species like some avian species (24,25), teleost fish (26), lizard (27), and frog (28).…”
Section: Discussionmentioning
confidence: 99%
“…In early embryonic development, the pancreas of the grass snake was formed mainly by ducts of different sizes. These results resemble the developmental patterns observed in embryonic pancreas of many other vertebrates species (Gupta, Uppal, Bansal, & Gupta, ; Hick et al, ; Westmoreland et al, ; Yee, Lorent, & Pack, ). Earlier research on Natrix embryos showed that these ducts emerged from the embryonic gut as a single short main pancreatic duct that branches into two smaller ducts: the main dorsal and main ventral duct (Kowalska et al, ).…”
Section: Discussionsupporting
confidence: 85%
“…Pancreatic cytodifferentiation studies in rats point out the importance that these microvesicles play in the “luminization” process, through which the epithelial cells cords begin to present a central lumen due to the convergence of vesicles in apical sense of the cells, similar to the arrangement of acini adults (Pictet, Clark, Williams, & Rutter, ) which is then confirmed to obtain larger lumens in chicken embryos. The events of epithelial cell differentiation in pancreatic cells in chickens are similar to that studied in humans (Manupati et al, ) and other mammals (Gupta, Uppal, Bansal, & Gupta, ), and follow the following sequence: transient stratification, polarity change of the cell, constriction of the asynchronous apical cell, organization of the “rosette” buds as well as formation and fusion of the vesicles forming the lumen.…”
Section: Discussionmentioning
confidence: 55%
“…Other mammals already studied show exocrine development around 14.5 days in pigs (Carlsson, Heller, Serup, & Hyttel, ), 75 days in sheep (Aldoretta, Carver, & Hay, ), day 10 in rabbits (Manakova & Titlbach, ). And 40 days in buffaloes (Gupta et al, ).…”
Section: Discussionmentioning
confidence: 99%